PERANCANGAN MEDIA EDUKASI BOARD GAME “INDOING” PEMBELAJARAN BAHASA INGGRIS PADA ANAK USIA 6 – 12 TAHUN - GUSRANDA, Ir. Drs. Heldi, M.Si., Ph.D., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Boardgame designing as educational media in the form of an entertaining game, is one of the alternative  learning media for teachers and students. The purpose of designing educational media boardgame is to  motivate activities, creativity, and sportsmanship in the development of science, skills, and attitudes in  children aged 6-12 years. The design methodology in designing boardgame through qualitative descriptivemethod with SWOT analysis approach (Strengt, Weakness, Opourtunities, Threats) can answer and solve problems and develop creative design idea. The result of boardgame design as main media with  specification in size (55x40) cm with game zone criterion in the form of world famous countries.  Supporting media in design consist of: rulebook (game manual), x-banner, t-shirt, keychains, mini  banners, posters and stickers.Keywords: Edukatif, Media, Board game